Population pharmacokinetics of ivermectin for the treatment of scabies in Indigenous Australian children. - Amanda Gwee; Stephen Duffull; Xiao Zhu; Steven Y C Tong; Noel Cranswick; Brett McWhinney; Jacobus Ungerer; Joshua Francis; Andrew C Steer (Public Library of Science (PLoS), 2020)
Ivermectin is a broad-spectrum antiparasitic agent used for the treatment and control of neglected tropical diseases. In Australia, ivermectin is primarily used for scabies and is licensed in children aged ≥5 years weighing >15 kg. However, young children, aged <5 years, are particularly vulnerable to scabies and its secondary complications. Therefore, this study aimed to determine an appropriate ivermectin dose for children aged 2 to 4 years and weighing ≤15 kg. We conducted a prospective, pharmacokinetic study of ivermectin in Indigenous Australian children aged between 5 and 15 years and weighing >15 kg. Doses of 200 μg/kg rounded to the nearest whole or half 3 mg tablet were given to children with scabies and ivermectin concentrations determined at two time points after dosing. A population pharmacokinetic model was developed using non-linear mixed effects modelling. A separate covariate database of children aged 2 to 4 years and weighing <15 kg was used to generate 1000 virtual patients and simulate the dose required to achieve equivalent drug exposure in young children as those aged ≥5 years. Overall, 26 children who had 48 ivermectin concentrations determined were included, 11 (42%) were male, the median age was 10.9 years and median body weight 37.6 kg. The final model was a two-compartment model with first-order absorption and linear elimination. For simulated children aged 2 to 4 years, a dose of 3 mg in children weighing 10-15 kg produced similar drug exposures to those >5 years. The median simulated area under the concentration-time curve was 976 μg∙h/L. Using modelling, we have identified a dosing strategy for ivermectin in children aged 2 to 4 years and weighing less than 15 kg that can be prospectively evaluated for safety and efficacy.